Laurence Oliphant: financial sources for his activities in Palestine in the 1880s - Amit, Thomas (Palestine exploration quarterly, 2007)
Laurence Oliphant's interest in the development o Jewish settlement in Ottoman Palestine preceded his interest in the plight of Jewish communities in Eastern Europe. While his intensive involvement in these matters is well known, especially in modern Israel, the fact that the funds for his largesse were contributed by the Christadelphian Brotherhood has not previously been published. The present article brings to light material from the archives of this sect, and thus, too, the motivation behind these efforts.